Heterogeneity in the Level of Technical Efficiency of Farms in the European Union Regions and its Relationship to Indebtedness - Staniszewski Jakub (Zagadnienia Ekonomiki Rolnej)
The purpose of the study is to determine the relationship between the level of farm indebtedness and their technical efficiency.